Financial Frictions and the Credit Transmission Channel: Capital Requirements and Bank Capital - Lucyna Gornicka; Sweder van Wijnbergen (Tinbergen Institute, 2013)
We investigate actual capital chosen by banks in presence of capital minimum requirements and ex-post penalties for violating them. The model yields excess capital that is always positive and increases during times of distress in the economy, which is in line with empirical evidence. Next, we show that in presence of ex-post violation penalties the introduction of the conservation buffer under Basel III will not contribute to lowering the pro-cyclicality of capital regulations. The countercyclical buffer proposed under Basel III is then even more desirable as it significantly attenuates fluctuations of actual capital also when the penalties are accounted for.
Keywords: G21; G28; E32; E44; 330; capital requirements; Basel regulatory framework; excess capital; countercyclical buffer; market discipline